Whole Lives Shapers of Modern Biography - Whittemore, Reed, 1919-2012.; Project Muse.; Project Muse. (2019)
Whittemore in this companion volume to Pure lives probes the often complex motives behind the relationships of modern biographers to their subjects. Examines among others, Thomas Carlyle, Leslie Stephen, Sigmund Freud, Leon Edel, and Richard Ellmann as biographers.
Carlyle and his great men -- Leslie Stephen's DNB and the Woolf rejoinders -- Sigmund Freud and his disciples -- American biography.
Companion vol. to: Pure lives.
Includes bibliographical references (pages 173-177) and index.
Description based on print version record.
Keywords: Geschichte (1850-1960); Geschichte (1800-1950); Biographers -- History; Biography (as a literary form); Geschiedschrijving; Biografieën.; Biografie; Geschichte; Biografische Literatur; Biography as a literary form; Biographers; Biographes -- Histoire; Biographie (Genre litteraire); Biographers -- History; Biography as a literary form; Englisch; USA; Biography; Electronic books; History; Electronic books